1972
DOI: 10.1111/j.1432-1033.1972.tb02554.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acylation on the Molecular Size of Insulin

Abstract: The tendency to aggregate a t neutral pH exhibited by zinc insulin, insulin and some N-acyl derivatives was studied with the aid of gel filtration. On Sephadex 6-75 and at an initial concentration of 1 mgjml, zinc insulin appeared t o possess an average molecular weight of 24000 and insulin an average molecular weight in the region of 12000. I n contrast, NUA1, NaB1, NEBz9-trisuccinylinsulin and N a A l , NUB1, N8B2Q-tricarbamylinsulin appeared predominantly monomeric with a molecular weight in the region of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1974
1974
1981
1981

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It was, however, the above author's contention that the removal of zinc was necessary to reduce the tendency towards self-association. In addition, Massey and Smyth [33] reported that zinc-free insulin revealed aggregates during gel filtration but to a lesser extent than zinc insulin. Sulphated insulin which is zinc-free tends to exist as a monomer [34], but this may be due to additional charges on the molecule introduced by the sulphate groups.…”
Section: Metal Ionsmentioning
confidence: 99%
“…It was, however, the above author's contention that the removal of zinc was necessary to reduce the tendency towards self-association. In addition, Massey and Smyth [33] reported that zinc-free insulin revealed aggregates during gel filtration but to a lesser extent than zinc insulin. Sulphated insulin which is zinc-free tends to exist as a monomer [34], but this may be due to additional charges on the molecule introduced by the sulphate groups.…”
Section: Metal Ionsmentioning
confidence: 99%